A Trojan Horse of a Word? "Development" in Bolivia’s Southern Highlands: Monocropping People, Plants and Knowledge - Walsh, Susan (Anthropologica, 2022)
Through a first-hand treatment of the humanitarian development assistance delivered to indigenous farmers in Potosi, Bolivia at the turn of this century, this paper challenges the all too common promotion of Western "capacity-building" programming and introduced technologies?particularly related to crop production?as "sacred cow" ingredients for sustain? able livelihoods among farmers on the margins. The Bolivian non-governmental organization (NGO) profiled paid insufficient attention to time-tested knowledge and practices that enabled survival in places where the natural world usually has the upper hand and where the conservation of plant genetic resources is fundamental to that survival. It would have been more suc? cessful, I suggest, had it turned the deficit argument?"the poor are lacking"?for development intervention on its head. It is not what farmers lacked, but what they already had?sophisti? cated but threatened livelihood strategies?that required endorsement and support.